Numerical Simulation of Heat Reduction With Use of Spike in Hypersonic Flow Based on Gas Kinetic Scheme - Chang-ya LIU; Di ZHOU; Zhi-liang LU; Tong-qing GUO (气体物理, 2023)
Based on the gas kinetic scheme (GKS), numerical simulation research on the thermal protection system with the spike was carried out from the independent flow field and the fluid-structure interaction. The reliability of the algorithm in independent flow field was first verified by using the standard cylindrical model, and then the effectiveness and mechanism of the heat reduction of spike were analyzed by comparing the aerothermal characteristics and the corresponding flow field characteristics of the cylindrical model without/with the spike. After verification by applying GKS to the coupled simulation of flow field/structure temperature field, the heat reduction performance of spike under the fluid-structure interaction was further analyzed. The results show that the heat reduction performance of spike increases with the advancement of the fluid-structure interaction time, which is beneficial to the long-term cruise flight of the hypersonic vehicle.